Correlates of depressive symptoms in individuals attending outpatient stroke clinics. Issue 1 (2nd January 2017) - Vermeer, Julianne; Rice, Danielle; McIntyre, Amanda; Viana, Ricardo; Macaluso, Steven; Teasell, Robert
Abstract: Background and purpose Depressive symptoms are common post-stroke. We examined stroke deficits and lifestyle factors that are independent predictors for depressive symptomology.Methods A retrospective chart review was performed for patients' post-stroke who attended outpatient clinics at a hospital in Southwestern Ontario between 1 January 2014 and 30 September 2014. Demographic variables, stroke deficits, secondary stroke risk factors and disability study measures [Patient Health Questionnaire-9 (PHQ-9) and Montreal Cognitive Assessment (MoCA)] were analyzed.Results Of the 221 outpatients who attended the stroke clinics (53% male; mean age = 65.2 ± 14.9 years; mean time post-stroke 14.6 ± 20.1 months), 202 patients were used in the final analysis. About 36% of patients (mean = 5.17 ± 5.96) reported mild to severe depressive symptoms (PHQ-9 ≥ 5). Cognitive impairment (CI), smoking, pain and therapy enrollment ( p < 0.01) were significantly associated with depressive symptoms. Patients reporting CI were 4 times more likely to score highly on the PHQ-9 than those who did not report CI (OR = 4.72). While controlling for age, MoCA scores negatively related to depressive symptoms with higher PHQ-9 scores associated with lower MoCA scores ( r = −0.39, p < 0.005).Conclusions High levels of depressive symptoms are common in the chronic phase post-stroke and were partially related to cognition, pain, therapy enrollment and lifestyle factors. Implications for Rehabilitation: Stroke patients who report cognitive deficits, pain, tobacco use or being enrolled in therapy may experience increased depressive symptoms. A holistic perspective of disease and lifestyle factors should be considered while assessing risk of depressive symptoms in stroke patients. Patients at risk for depressive symptoms should be monitored at subsequent outpatient visits.